2019
DOI: 10.1039/c9cp03348c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of large clusters of CO2around anions: DFT study reveals cooperative CO2adsorption

Abstract: The cooperative O⋯C secondary interactions compensate for the diminishing effect of primary anion⋯C interactions in anionic clusters of CO2 molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…The DFT method M06L/6–311++G(d,p) 51,52 as implemented in Gaussian09 program package 53 is used to optimize all the ring molecules and their water complexes (Table S2). The MESP 54 V (r) at a point r is defined in Equation () where V()rgoodbreak=ANnormalZnormalArnormalRnormalAgoodbreak−normalρ()normalr'd3normalr'rr' Z A is the charge on nucleus A located at R A , and ρ(rˈ) is the molecule's continuous electronic density and N is the total number of nuclei.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DFT method M06L/6–311++G(d,p) 51,52 as implemented in Gaussian09 program package 53 is used to optimize all the ring molecules and their water complexes (Table S2). The MESP 54 V (r) at a point r is defined in Equation () where V()rgoodbreak=ANnormalZnormalArnormalRnormalAgoodbreak−normalρ()normalr'd3normalr'rr' Z A is the charge on nucleus A located at R A , and ρ(rˈ) is the molecule's continuous electronic density and N is the total number of nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…The DFT method M06L/6-311++G(d,p) 51,52 as implemented in Gaussian09 program package 53 is used to optimize all the ring molecules and their water complexes (Table S2). The MESP 54 V(r) at a point r is defined in Equation ( 1) where…”
Section: Methodsmentioning
confidence: 99%
“…The M06L is regarded as a robust DFT method in overall performance for the optimization of organometallic, inorganic systems and for the study of noncovalent interactions, especially for moderatesized and large systems. [48][49][50][51] A recent benchmark study from our group has shown the accuracy of this method in calculating the interaction energy of anionic fullerene systems for Grimme's dispersion correction. 45,52,53 The reaction of 'n' times 1,3dimethyl-2,3-dihydro-2-cyano-imidazole (IMCN) with C 60 yields the ion pair complex (IM + ) n Á Á Á(C 60 (CN) n ) nÀ .…”
Section: Methodsmentioning
confidence: 99%
“…[ 47 ] In recent years, more attention was paid to the tetrel bond involving CO 2 in which the carbon atom of CO 2 acts as the tetrel donor. [ 48–57 ] On the other hand, the oxygen atom of CO 2 can also act as a base to engage in tetrel bonds, on which little study is focused. The separation, absorption, capture, and conversion of CO 2 have been extensively studied with silicon‐containing materials.…”
Section: Introductionmentioning
confidence: 99%